POSTCOLONIALISM IN ORHAN PHAMUIC'S SNOW : A LITERARY ANALYSIS - Siyaswati, Siyaswati (LPPM Universitas PGRI Adi Buana Surabaya, 2012)
The purpose of this paper is to reveal the postcolonialism approach a literary study in Novel Snow by Orhan Phamuk. Post colonialism is inspired by Orientalism and produced due to social injustice in colonized countries.